LANGUAGE STYLE OF HUMOR ON STAND-UP COMEDY VIDEO - Merry Rullyanti; Nurdianto Nurdianto (JOALL (Journal of Applied Linguistics and Literature), 2019)
This research explained about language styles which used in stand-up comedy script brought by Chris Rock. Chris Rock owns famous joke material that is affected by the black comedy pioneers like Richard Pryor and Redd. He attacked the subject of much avoided by comics such as politics, race and celebrity. Openness and honesty witch extremely bold that what makes Chris Rock as one of the most successful and a famous comic in modern comedy. Chris Rock is known for his insulting comedian, he is also known for using satire and surreal in his joke. Language style has several functions in its uses. Stand up comedy brought by Chris Rock is usually shows about the different in human right between black and white skin.Based on the description above, the researcher decided to research language style in stand-up comedy brought by Chris Rock. In this research the researcher uses Keraf (2007) to analyze the language styles. This research is a qualitative descriptive research. This research source of data is stand-up comedy script with tittle “kill the messenger” brought by Chris Rock. Based on research, there are 2 language styles used in “kill the messenger”, there are 10 rhetorical language styles and 17 figurative language styles. Based on the data, hyperbole rhetorical language style is dominantly used in “kill the messenger”. And Epithet figurative language is dominantly used too.The reason is because Chris Rock is still try to persuade the white skin American to be humble to black skin American and must respect to each other. Keywords: Language Styles, Humor, Stand-Up Comedy